Antiphospholipid antibodies predict progression of abdominal aortic aneurysms. - Christina Duftner (Public Library of Science (PLoS), 2014)
Antiphospholipid antibodies (aPLs) frequently occur in autoimmune and cardiovascular diseases and correlate with a worse clinical outcome. In the present study, we evaluated the association between antiphospholipid antibodies (aPLs), markers of inflammation, disease progression and the presence of an intra-aneurysmal thrombus in abdominal aortic aneurysm (AAA) patients. APLs ELISAs were performed in frozen serum samples of 96 consecutive AAA patients and 48 healthy controls yielding positive test results in 13 patients (13.5%) and 3 controls (6.3%; n.s.). Nine of the 13 aPL-positive AAA patients underwent a second antibody testing >12 weeks apart revealing a positive result in 6 cases. APL-positive patients had increased levels of inflammatory markers compared to aPL-negative patients. Disease progression was defined as an increase of the AAA diameter >0.5 cm/year measured by sonography. Follow-up was performed in 69 patients identifying 41 (59.4%) patients with progressive disease. Performing multipredictor logistic regression analysis adjusting for classical AAA risk factors as confounders, the presence of aPLs at baseline revealed an odds ratio of 9.4 (95% CI 1.0-86.8, p = 0.049) to predict AAA progression. Fifty-five patients underwent a computed tomography in addition to ultrasound assessment indicating intra-aneurysmal thrombus formation in 82.3%. Median thrombus volume was 46.7 cm3 (1.9-377.5). AAA diameter correlated with the size of the intra-aneurysmal thrombus (corrcoeff = 0.721, p<0.001), however neither the presence nor the size of the intra-aneurysmal thrombus were related to the presence of aPLs. In conclusion, the presence of aPLs is associated with elevated levels of inflammatory markers and is an independent predictor of progressive disease in AAA patients.